2014
DOI: 10.3233/thc-130770
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of autologous transfusion system in primary total hip and knee arthroplasty

Abstract: BACKGROUND: Autologous transfusion has become a cost-efficient and useful option in the treatment of patients with high blood loss following major orthopaedic surgery. However, the effectiveness of autologous transfusion in total joint replacement remains controversial. OBJECTIVE: The current study analyzed the efficacy of autologous transfusion with washed shed blood (WSB) in primary total knee and total hip arthroplasty (TKA, THA). METHODS: Between January 2011 and December 2011, patients being treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Gargaro and Walls[ 14 ] compared the ABT rates among patients who underwent THR with (n=32) and without (n=32) intraoperative use of cell saver. In line with Schneider et al,[ 9 ] they did not find a significant difference between these patient groups. [ 14 ] In contrast, Guerra and Cuckler[ 11 ] stated that the use of cell saver during primary THR surgeries led to a 40% decrease in the rate of ABTs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Gargaro and Walls[ 14 ] compared the ABT rates among patients who underwent THR with (n=32) and without (n=32) intraoperative use of cell saver. In line with Schneider et al,[ 9 ] they did not find a significant difference between these patient groups. [ 14 ] In contrast, Guerra and Cuckler[ 11 ] stated that the use of cell saver during primary THR surgeries led to a 40% decrease in the rate of ABTs.…”
Section: Discussionsupporting
confidence: 88%
“…[6] Therefore, efforts spent to date to develop strategies for reducing ABT rates during or after THR are justified. [5,[7][8][9][10][11][12][13][14][15] Several preoperative, intraoperative, and postoperative blood management protocols have been proposed. Preoperative preventions include hemoglobin (Hgb) optimization in anemic patients using erythropoietin (EPO) injection and intravenous iron replacement therapy.…”
mentioning
confidence: 99%
“…There are contradictory findings in the literature regarding the use of cell salvage in TKA. Schneider et al[ 19 ] reported that cell salvage had no beneficial effect on the rate of allogeneic blood transfusion. In contrast, Park et al[ 20 ] showed a significant reduction in blood transfusion in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning AT, patient's blood can be collected using different strategies among which the most frequently applied are the following ones: 1) preoperative autologous collection/donation (PAD); 2) acute normovolemic hemodilution (ANH); and 3) perioperative blood recovery/salvage (PBR). In addition, the scheme of PBR includes: a) intraoperative blood collection/salvage (IBC) from the surgical field, and b) postoperative blood collection/drainage (PBC) by aspiration 1,[14][15][16][17][18][19][20][21][22] . Independently or combined, these AT-strategies proved to reduce the needs for allogeneic blood in elective surgery.…”
Section: Regardless Of the Implementation Of Different Effective Prevmentioning
confidence: 99%
“…Opinions regarding efficiency of PBC in orthopedic surgery are not unanimous and the following should be taken into consideration: 1) prospect studies to illustrate the benefits of transfusion of "saved" blood; b) make analyses of risks of transfusion of unprocessed blood, taking into special consideration possible contamination of blood with bacteria or chemical agents (e.g. metylmetakrylat) and 3) analysis of cost vs benefit aspects 6,[14][15][16][17][18][19][20][21][22] .…”
Section: Perioperative Blood Recovery/salvagementioning
confidence: 99%